Genetics of Pheochromocytoma and Paraganglioma in Spanish Patients - Cascón, Alberto; Pita, Guillermo; Burnichon, Nelly; Landa, Iñigo; López-Jiménez, Elena; Montero-Conde, Cristina; Leskelä, Susanna; Leandro-García, Luis Javier; Letón, Rocío; Rodríguez-Antona, Cristina; Díaz, José Ángel; López-Vidriero, Emilio; et al. (The journal of clinical endocrinology and metabolism, 2009)
Context: The presence of familial history in pheochromocytoma/paraganglioma patients, including syndromic antecedents, leads in the majority of cases to a positive genetic testing for mutations in one of the major susceptibility genes described so far. Furthermore, it has been reported that in the absence of familial antecedents, about 11–24% of patients also carry a mutation in one of these related genes. In these cases, other clinical aspects like bilaterality, multiplicity, location of the tumors, or age at onset can help to recognize the underlying genes involved. Objective: The objective of the study was to discuss clinical criteria helpful in the genetic diagnosis, placing special emphasis on apparently sporadic cases. Design: Two hundred thirty-seven nonrelated probands were analyzed for the major susceptibility genes: VHL, RET, SDHB, SDHC, and SDHD. Genetic characterization included both point mutation analysis and gross deletions in the SDH genes performed by multiplex PCR. Results: As expected, all syndromic probands were genetically diagnosed with a mutation affecting either RET or VHL. A total of 79.1% (19 of 24) and 18.4% (31 of 168) of patients presenting with either nonsyndromic familial antecedents or apparently sporadic presentation were found to carry a mutation in one of the susceptibility genes. Finally, we found a Spanish founder effect for two mutations: SDHB c.166_170delCCTCA and SDHD c.129G>A. Conclusions: Germline mutations are rare in apparently sporadic probands diagnosed after age 40 yr (3.9% in our series) and mainly involve SDHB. Therefore, we recommend prioritizing SDHB genetic testing in patients developing isolated tumors at any age, especially those with extraadrenal location or malignant behavior.